Performance and environment as objectives in multi-criterion optimization of steam injected gas turbine cycles - Kayadelen, Hasan Kayhan; Ust, Yasin (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
Rapidly growing demand for gas turbines promotes research on their performance improvement and reducing their exhaust pollutants. Even small increments in net power or thermal efficiency and small changes in pollutant emissions have become significant concerns for both new designs and cycle modifications. To fulfill these requirements an accurate performance evaluation method which enables to see the effects on the exhaust gas composition is an important necessity. To fill this gap, a thermo-ecologic performance evaluation approach for gas turbine cycles with chemical equilibrium approximation which enables performance and environmental aspects to be considered simultaneously, is presented in this work. Steam injection is an effective modification to boost power and limit NOx emissions for gas turbine systems. Steam injection also increases thermal efficiency so less fuel is burnt to maintain the same power output. Because of its performance related and environmental advantages, presented approach is applied on the steam injected gas turbine cycle and a precise multi-criterion optimization is carried out for varying steam injection, as well as equivalence and pressure ratios. Irreversibilities and pressure losses are also considered. Effects of each parameter on the net work and thermal efficiency as well as non-equilibrium NOx and CO emissions are demonstrated. Precision improvement of the presented thermo-ecological model is shown and two main concerns; constant turbine inlet condition for higher net work output and constant net work output condition for lower fuel consumption are compared. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Gas turbines; Thermo optimization; Emissions; Engine simulation/modeling; Steam injection; Thermo-ecologic analysis; EQUILIBRIUM COMPOSITION; WATER INJECTION; DIESEL-ENGINE; COMBUSTION; TEMPERATURE; PRODUCTS; SYSTEM; Thermodynamics; Energy & Fuels; Engineering; Mechanics